Biobanking of gynecologic cancer biospecimens: Development, quality control, and translational applications - Jue Young Kim; Yoo-Kyung Lee; Ha-Yeon Shin; Yoon Joo Kim; Mi Ae Jeon; Wookyeom Yang; Anna Jun; Kyungmin Kim; Hanbyoul Cho; Min-A Kim; Jae-Hoon Kim (PLoS ONE, 2026)
Introduction This study presents a nationwide infrastructure for the collection and utilization of gynecologic cancer biospecimens, established through the Korea Biobank Project. We comprehensively describe the biobanking strategy, quality control protocols, and development of secondary resources to support future translational and discovery-based research. Methods We established a gynecologic cancer biobank within the Korea Biobank Project (KBP) through a multi-institutional consortium. Biospecimens, including blood, tumor tissue, urine, and ascites, were collected from 294 patients with endometrial, cervical, or ovarian cancers. Pre-analytical variables were documented using the Standard PREanalytical Code (SPREC), and all samples were tracked with 2D barcodes. Secondary resources were developed, including whole-genome sequencing (WGS) datasets, immortalized human ovarian surface epithelial (IHOSE) cell lines, patient-derived xenografts (PDX), tumor organoids, and tissue microarrays (TMAs). Results A total of 6,168 biospecimens were archived. WGS was performed on 386 cancer samples, including 172 paired tumor–normal sets. Four IHOSE cell lines were authenticated and validated for stability, 14 PDX models retained histological fidelity across passages, and patient-derived ovarian cancer organoids demonstrated drug sensitivity consistent with clinical response patterns. TMAs were constructed from 519 tumors, supporting large-scale molecular profiling. Industry collaborations further highlighted the translational utility of these resources. Conclusions This study describes the development and application of a gynecologic cancer biobank that integrates standardized biospecimen collection, rigorous QC, and the generation of diverse secondary resources. By linking these resources with clinical and epidemiological data, the biobank provides a scalable and accessible platform for precision oncology and academic–industry collaboration.